Economic Burden of Denatured Alcohol-Induced Burns: A 20-Year Retrospective Study - Venturi, Michela; Bruzziches, Francesco; Orlandi, Catuscia; Altini, Mattia; Rubegni, Pietro; Melandri, Davide (Frontiers in Medicine, 2022)
Burn care has rapidly improved over the past decades but health innovations are expensive. We present the first study focusing on the economic burden of exclusively denatured alcohol-induced burns. The goal of this study was to determine the costs for the public health system due to inpatients’ burn care because of these specific burns. Moreover, we aimed to observe the incidence of methylated spirit-related burns over the past 20 years. We performed an observational retrospective study in our Burn Unit including all patients with a denatured alcohol-related burn injury from January 1, 2001, to December 31, 2020. 503 patients with a mean burn size of 24% were hospitalized; the mean annual total costs per patient was 43,879.00 € varying from 31,518 € to 63,274.00 €; the total costs for denatured alcohol-related burns during the period 2001-2020 was 21,145,076.00 €. We noted an increasing incidence of denatured alcohol-related burns and related costs over the years, especially in the last decade. Our results highlight that burns by methylated spirits are still a real and expanding problem. Therefore, the authorities should focus on sales rules, on the characteristics of the containers and on the education of people who misuse denatured alcohol, based on historical habits of use. To reduce the socio-economic costs of burns, future intervention strategies and studies also from the Dermatology community and Burn Specialists should focus on prevention programs, prompt wound healing, shortening the length of hospital stay and enabling a quick return to work improving the burn patient outcome.